Electrochemical Fluorescence Switching in Rhodamine–Ferrocene Dyads: Spatiotemporal Control in Biomimetic Membranes - Ning Jiang; Lorenzo Meneghelli; Niccolo Dipace; Carolina Chieffo; Bixente Carré; Ambre Etcheverria; Manuel Pedrón; Manon Guille-Collignon; Frédéric Lemaître; Frédéric Labat; Ilaria Ciofini; Blaise Dumat; et al. (Journal of the American Chemical Society, 2026)
Abstract The electrochemical control of fluorescence has been extensively developed in homogeneous media, yet its implementation within electrically insulating lipid bilayers remains largely unexplored. Here we establish that an electrochemically gated fluorescence switch can be implemented in individual giant unilamellar vesicles using a rhodamine–ferrocene dyad that modulates emission through redox-controlled photoinduced electron transfer. A membrane-anchored derivative enables direct visualization of reversible fluorescence activation under electrochemical bias. Remarkably, the switching is strictly leaflet-selective and occurs only for dyads exposed to the electrode interface, highlighting the insulating nature of lipid bilayers. Furthermore, membrane surface charge critically governs the switching efficiency and induces pronounced kinetic asymmetry between oxidation and reduction processes, revealing the key role of interfacial electrostatic interactions in redox-controlled emission. These results establish electrochemical fluorescence modulation in membranes as a spatially and electrostatically gated interfacial process and define general principles for redox-responsive probes operating in soft interfaces, such as lipid membranes.